Literature Study on the Impact of Congregational Morning Prayer on Academic Anxiety: A View on Psychospiritual and Psychoneuroimmunology in Students - Syafi'i, Muhammad Hisyam; Mulya, Adi (Universitas Muhammadiyah Yogyakarta, 2024)
The practice of congregational morning prayer holds significant importance in both the context of worship and globally, as it promotes positive impacts. From a psychospiritual perspective, congregational prayer can be therapeutical in the modern era. Anxiety is a human adaptation response to any imminent or uncertain event that can occur in daily life situations. During the preparation for the thesis, most university students experienced several symptoms of anxiety (physical, cognitive, emotional, and affective symptoms). These symptoms can affect the students' cognitive ability, intelligence, family demands on campus, and social interactions. This study aimed to describe efforts to overcome academic anxiety among university students through psychospiritual and psychoneuroimmunological points of view. The study used a library research approach by gathering credible sources from books, scientific articles, documents, and previous research. The findings of this study showed that congregational prayers can be an effort to relieve academic anxiety among students.